FAITH AND FINANCE: UNDERSTANDING MUSLIM MILLENNIALS’ SHIFT TOWARD RIBA-FREE INVESTMENTS - Hidayatullah, Syarif; Suherlan, Ade; Khalid, Radhwan Hazim (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2025)
This study aims to present the main factors that affect riba-free Investment Preference with an emphasis on religiosity, financial literacy, and factors derived from Planned Behavior Theory (TPB). The cross-sectoral quantitative survey methodology used targets the Muslim millennial generation domiciled in DKI Jakarta. This study used a sample of 385 respondents. The key variables measured include investment preferences in sharia and conventional products. Data analysis involves descriptive statistics, validity and reliability tests, comparative tests, and Covariance-Based Structural Equation Models (CB-SEM). The results show a statistically significant preference among the millennial generation of Jakarta Muslims towards riba-free investment products compared to conventional alternatives. Religiosity emerged as the strongest positive predictor of riba-free investment preferences. Attitudes towards sharia investment and perceptions of behavior control also have a significant positive effect. Financial literacy showed a positive but relatively weak influence, while subjective norms and risk tolerance did not significantly predict preference in the final model. The overall model explains most of the variation in preferences. This research contributes to the understanding of investment behavior among Millennial Muslims in accordance with Islamic principles.